Effects of repetitive high energy pulsed power (RHEPP) irradiation on sensory attributes, color, and shelf life of ground beef - Hachmeister, K.A.; Kropf, Donald H.; Gill, V.S.; Kaye, R.J.; Hunt, Melvin C.; Marsden, James L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We investigated the effects of packaging atmosphere and three levels of irradiation dose (Repetitive High Energy Pulsed Power, - RHEPP) on microbial populations, vitamin retention, and display color attributes of ground beef patties stored either chilled or frozen. Beef knuckles and beef fat were coarsely ground, sampled and analyzed to achieve 20% fat, mixed, ground through a 1/8 in. plate, and processed into 1/4-lb patties, which were sealed either aerobically or nitrogen-flushed. Patties were not irradiated or irradiated to 1.5 or 3.0 kGy, chilled, and displayed at 37 ± 4EF for 6 days under 150 foot-candles of Deluxe Warm White fluorescent lighting in an open-top display case defrosted at 12 hour intervals. Hunterlab Instrumental color was measured daily. The experiment was replicated three times. Aerobically packaged patties were lighter, more yellow, more discolored, and less red (all P<.05) than nitrogen-flushed patties over the 6-day display. Nitrogen-flushing for irradiated patties resulted in higher (P<.05) retention of thiamin, but riboflavin was not affected (P>.05). At $ 1.5 kGy, aerobic and lactic acid bacteria were reduced (P<.05), and no E. coli and coliforms survived. Nitrogenflushing combined with irradiation resulted in more stable, intensely red colored patties, which retained more thiamin. The effect of irradiation on various flavor notes was minimal and generally diminished in nitrogen-flushed compared to aerobic packages.
Keywords: Beef; Irradiation; Ground Beef; Color; Vitamin retention